Extra‐pair paternity as a strategy to reduce the costs of heterospecific reproduction? Insights from the crow hybrid zone. (16th March 2020) - Knief, Ulrich; Bossu, Christen M.; Wolf, Jochen B.W.
Abstract: Within hybrid zones of socially monogamous species, the number of mating opportunities with a conspecific can be limited. As a consequence, individuals may mate with a heterospecific (social) partner despite possible fitness costs to their hybrid offspring. Extra‐pair copulations with a conspecific may thus arise as a possible post hoc strategy to reduce the costs of hybridization. We here assessed the rate of extra‐pair paternity in the hybrid zone between all‐black carrion crows ( Corvus (corone) corone ) and grey hooded crows ( C. (c.) cornix ) and tested whether extra‐pair paternity (EPP) was more likely in broods where parents differed in plumage colour. The proportion of broods with at least one extra‐pair offspring and the proportion of extra‐pair offspring were low overall (6.98% and 2.90%, respectively) with no evidence of hybrid broods having higher EPP rates than purebred nests. Abstract : All‐black carrion crows and grey hooded crows hybridize in a narrow zone in Central Europe, despite possible fitness costs to their hybrid offspring. Extra‐pair copulations with a conspecific may be a post‐hoc strategy to reduce the costs of hybridization. Using genetic data from the hybrid zone, we find that the overall extra‐pair paternity (EPP) rate is low and that hybrid broods do not have higher EPP rates than purebred nests.